Itchy Capillary Malformations: Unusual Appearance of Meyerson Phenomenon, a Case Series - Manuel Sanchez-Diaz; Trinidad Montero-Vilchez; Luis Salvador-Rodriguez; Alejandro Molina-Leyva; Salvador Arias-Santiago; Jesús Tercedor-Sanchez (MDPI AG, 2021)
Meyerson phenomenon, also known as "halo-eczema," has been widely described over melanocytic and non-melanocytic lesions. However, its appearance over vascular anomalies is rarely observed and could lead to diagnostic errors. A case study of five patients aged between four months and two years is reported. These patients developed unique erythematous and pruritic scaly patches, being diagnosed and treated as fungal infections. Due to the lack of response to the treatment, they were referred to the pediatric dermatology practice, where the diagnosis of Meyerson phenomenon over capillary malformations was made. Topical treatment with corticosteroids led to improvement in all cases. Although Meyerson phenomenon developing over vascular anomalies is a rare condition, it is important for pediatricians and dermatologists to assess it as a part of the differential diagnosis when treating a patient with skin lesions. Recognizing this phenomenon will prevent diagnostic and therapeutic errors.